2021
DOI: 10.21272/mmi.2021.1-09
|View full text |Cite
|
Sign up to set email alerts
|

Innovation capability of the company: the roles of leadership and error management

Abstract: Extensive research has been conducted promoting empowerment, inclusive decision making, and self-determination by employees. However, where does an organization initiate change if employees stay in their comfort zone and rather have a work-to-rule mentality? They just do not take over responsibility and the power they are given. The inductive case study involved first-hand data about leader-member exchange and corporate culture. A qualitative research approach was selected by employing personal construct psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In this way, error management is not only important in organizations that deal with potentially catastrophic errors, such as the field of aviation, medicine, or nuclear plants, but also in organizations where errors are related to minor harm. All errors cause inefficiencies, and learning from them makes practices more efficient and innovative (Birkinshaw et al, 2008; Bundtzen & Hinrichs, 2021; van Dyck et al, 2005), and relatedly, the quality of internal processes and service delivery increases. At the same time, in the age of algorithmic decision-making and automated processes, errors do usually not just concern single cases, where a case worker made a wrong decision by applying the wrong rules for example, but a bigger number of cases handled by a wrongly trained or programmed algorithm, leading to major harm (as seen for example in the so-called Dutch childcare benefit scandal, Alon-Barkat & Busuioc, 2023).…”
Section: State Of Researchmentioning
confidence: 99%
“…In this way, error management is not only important in organizations that deal with potentially catastrophic errors, such as the field of aviation, medicine, or nuclear plants, but also in organizations where errors are related to minor harm. All errors cause inefficiencies, and learning from them makes practices more efficient and innovative (Birkinshaw et al, 2008; Bundtzen & Hinrichs, 2021; van Dyck et al, 2005), and relatedly, the quality of internal processes and service delivery increases. At the same time, in the age of algorithmic decision-making and automated processes, errors do usually not just concern single cases, where a case worker made a wrong decision by applying the wrong rules for example, but a bigger number of cases handled by a wrongly trained or programmed algorithm, leading to major harm (as seen for example in the so-called Dutch childcare benefit scandal, Alon-Barkat & Busuioc, 2023).…”
Section: State Of Researchmentioning
confidence: 99%
“…Research conducted by Bundtzen and Hinrichs [42] mapped the relationship between transformational leadership style and resilience with psychological empowerment as a mediator. The research of Taj et al, [43] stated that psychological empowerment has a positive significance to resilience.…”
Section: H6: Psychological Empowerment Mediates the Influence Between...mentioning
confidence: 99%
“…Frese and Keith (2015) posit that people take more initiatives and act proactively in organizations where error management is high. It is suggested that the atmosphere created by error management where employees look for assistance for the errors promotes employees' proactive behaviors (Bundtzen and Hinrichs, 2021). Farnese et al (2020) reveal that employees who consider errors as inevitable and evaluate them as commensurable risks approach errors positively.…”
Section: Error Management and Eomentioning
confidence: 99%